Hubungan Kelengkapan Kunjungan ANC, Umur Ibu Hamil dan Konsumsi Fe - Kukuh Purwo Saputro; Mexitalia Setiawati; Suhartono Suhartono; Dwi Sutiningsih (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Neonatal deaths are those that occur in the neonatal period when the baby is born up to 28 days (0-28 days). Neonatal mortality contributes to 56% of infant deaths due to complications such as BBLR, asphyxia, and infections that should be prevented by taking into account the condition of the mother before and during pregnancy because it will determine the condition of the baby being born. This study aimed to determine maternal factors associated with neonatal mortality.Methods: The design of an analytic observational study using a case-control. The population of the study was infants born in Banjarnegara District in 2018. The sample of the study was 65 cases and 65 controls taken by simple random sampling. The data were analyzed univariate and bivariate.Result: The results showed a significant relationship between the completeness of the ANC visit (p = 0.029; OR = 3.6 (95% CI = 1.222-10.595)) and the consumption of Fe <90 tablets (p = 0.0001; OR = 4, 1 (95% CI = 1,942-8,816)) with neonatal mortality. There was no relationship between the age of pregnant women <20 years old and >35 years old with neonatal mortality.Conclusion: The conclusion of this study is the variables that are statistically related to neonatal mortality are completeness of ANC visit and consumption of Fe <90 tablets.